Faraday rotations, ellipticity, and circular dichroism in magneto-optical spectrum of moiré superlattices*Project supported by the National Natural Science Foundation of China (Grant Nos. 12050410228 and 12074260) and the Fund from the Science and Technology Commission of Shanghai Municipality, China (Grant No. 19ZR1436400). (July 2021) - Crosse, J A; Moon, Pilkyung
Abstract : We study the magneto-optical conductivity of a number of van der Waals heterostructures, namely, twisted bilayer graphene, AB–AB and AB–BA stacked twisted double bilayer graphene and monolayer graphene and AB-stacked bilayer graphene on hexagonal boron nitride. As the magnetic field increases, the absorption spectrum exhibits a self-similar recursive pattern reflecting the fractal nature of the energy spectrum. Whilst twisted bilayer graphene displays only weak circular dichroism, the other four structures display strong circular dichroism with monolayer graphene and AB-stacked bilayer graphene on hexagonal boron nitride being particularly pronounced owing to strong inversion symmetry breaking properties of the hexagonal boron nitride layer. As the left and right circularly polarized light interact with these structures differently, plane-polarized incident light undergoes a Faraday rotation and gains an ellipticity when transmitted. The size of the respective angles is on the order of a degree.